What Is More Important: The Age and Size of a University or Its Accreditation in Gauging Which of Their Degrees Better Represents Value for Money (Quality and Recognition)? - Paul (Sr.), Stanley A. V.; Gjorgov, Emil; English, Ivor B.; Paul (Jr.), Stanley A. V.; Rajkumar, Yogita; Glasgow, Roslyn (Stallion Journal for Multidisciplinary Associated Research Studies, 2023)
The size and age of the university are critical factors as they indicate history and reputation. However, accreditation provides a standardized quality measure and a tangible assessment of the program's adherence to established benchmarks and standards. In the context of which is more essential, either the age and size of a university or its accreditation, in gauging which of their degrees better represents value for money (quality and recognition), the current study assesses the role of accreditation in guaranteeing educational standards and enhancing the value of degrees, and investigate the impact of age and size on educational quality and recognition. The research paper uses a content analysis technique to review a vast range of academic literature, exploring existing studies to find answers to the problem. It was revealed that accreditation is more important than a university's size and age in gauging the value for money of its degree as it ensures that the university meets specific standards and quality recognition, assuring students regarding the credibility and value of the degree awarded.